JOSÉ J. QUEIROZ’S EPISTEMOLOGICAL DIALOGUE WITH EDGAR MORIN - Stigar, Robson; Ruthes, Vanessa Roberta Massambani (Seven Editora, 2026)
This article aims to briefly present the epistemological dialogue between José J. Queiroz and Edgar Morin. Queiroz was one of the first Brazilian researchers to bring Morin’s thought to PUCSP (Pontifical Catholic University of São Paulo) and to disseminate it in its essence and neutrality. To understand this relationship, we will examine the biographies of Edgar Morin and José J. Queiroz, where we will observe that they share the same way of thinking about Society, Education, and the Human Being, being guided by the Epistemology of Complexity Theory, which contributes to an interdisciplinary approach. Both were enthusiastic and visionary in the field of Education, this being a dialogical relationship, in which the whole and the part have the same value in the construction of Postmodern thought. An enthusiast of Complex Thought, Queiroz also believed in the existence of Postmodernity.